Sanksi Pidana Terhadap Pembuat Stiker Whatsapp yang Menyerang Personal Seseorang - Gede Oka Swarbhawa; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Warmadewa Press, 2022)
The internet is something that is very much needed by the community, which has a positive and negative impact on its users. The negative impact that can be felt now is the rise of crime on social media such as insults. Insults through WhatsApp communication media generally attack a person's good name or honor which is carried out through sticker media. The purposes of this study are to reveal the legal arrangements against WhatsApp sticker makers who attack someone's personal and criminal sanctions against WhatsApp sticker makers who attack someone's personal. This type of research is normative legal research with a case and legislation approach. The data collection technique was carried out using library techniques by collecting primary and secondary sources of legal material. After the data is collected, then the data is analyzed qualitatively and presented in descriptive form. The results of the study reveal that the government provides legal arrangements for WhatsApp sticker makers who attack someone's personal, where the government has regulated and provided protection against insults in electronic media, especially WhatsApp communication media, namely in articles 310 and 315 of the Criminal Code and in Law Number 11 of 2008 regarding Electronic Transaction Information. Criminal sanctions against WhatsApp sticker makers who attack a person's personality are regulated in Article 45 paragraph (1) which is punishable by a maximum imprisonment of 6 (six) years and/or a maximum fine of Rp. 1.000.000.000,00 (one billion rupiah).